PENINGKATAN KETERAMPILAN ISTRI NELAYAN DESA ALUE AMBANG MELALUI PELATIHAN PEMBUATAN TERASI IKAN HASIL TANGKAP SAMPING - Novi Sri Lestari; Nabila Ukhty; Yasrizal Yasrizal (Universitas Teuku Umar, 2022)
The People of Alue Ambang Village mostly work as fishermen with their main catch were shrimp. Apart from the main catch, the catches of fishermen in Alue Ambang Village were fish by-catch (HTS). Utilization of fish by catch by into shrimp paste is an alternative for increase the income of fishermen’s household. The purpose of this training is to improve the skills of the women of Alue Ambang Village through making the shrimp paste from fish by catch. The activity was carried out in Alue Ambang Village, Teunom District, Aceh Jaya Regency. The activities were carried out in three meetings, the first meeting was the socialization of fermented products, the second meeting was training of making shrimp and the third meeting was socialization of packaging and labeling procedures for shrimph paste products. The training activities were attended by enthusiastic participants from start to finish. Achievements obtained from this activity were participants being able to utilize fish by catch into the product with a higher selling value, being able to produce the shrimp paste based on fish by catch as a household business independently, and being able to understand the importance of using packaging and labels to product development.